Accidentally...cimil?--an accidentally yours novella ebook Accidentally yours series, book 4.5. - Pamfiloff, Mimi Jean (Accidentally Yours, 2014)
A Crazy Kind of Love Meet Cimil. Yeah, she's the Goddess of the Underworld, harbinger of all things evil and deadly, yadda, yadda . . . but she's also crazy fun! While minding her own business in Giza, Egypt, around 3000 BC (give or take a few centuries), she spots the hottest mortal her immortal eyes have ever seen. And he's not just any guy-he's the strong, powerful pharaoh who's fallen madly in love with her. But when he kills her pet unicorn, Cimil vows revenge, even if takes thousands of years to get even. When Roberto meets Cimil, the king knows she's his soul mate. It isn't just her beautiful eyes or gorgeous body, but the godly power he feels simmering just beneath her fun-loving surface. They were the perfect couple . . . until the dead unicorn thing. Now after four thousand years, Roberto crosses paths with Cimil again, and his love for her is stronger than ever. But can he prove that he can once again be trusted with her heart? Approx. 34,000 words. The Accidentally Yours Series BOOK 1: Accidentally in Love with...a God? BOOK 2: Accidentally Married to...a Vampire? BOOK 3: Sun God Seeks...Surrogate? BOOK 3.5: Accidentally...Evil? (a Novella) BOOK 4: Vampires Need Not...Apply? BOOK 4.5: Accidentally...Cimil? (a Novella) BOOK 5: Accidentally...Over? (Coming in August 2014)